The Ovidian vogue: literary fashion and imitative practice in late Elizabethan England - Moss, Daniel D. (University of Toronto Press, 2014)
"The Roman poet Ovid was one of the most-imitated classical writers of the Elizabethan age and a touchstone for generations of English writers. In The Ovidian Vogue, Daniel Moss argues that poets appropriated Ovid not just to connect with the ancient past but also to communicate and compete within late Elizabethan literary culture